2006
DOI: 10.1021/jm0511435
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole−Dioxolane Compounds as Isozyme-Selective Heme Oxygenase Inhibitors

Abstract: Several imidazole-dioxolane compounds were synthesized and evaluated as novel inhibitors of heme oxygenase (HO). These compounds, which include (2R,4R)-2-[2-(4-chlorophenyl)ethyl]-2-[(1H-imidazol-1-yl)methyl]-4-methyl-1,3-dioxolane (1) hydrochloride, are structurally distinct from metalloporphyrin HO inhibitors and lack the aminothiophenol moiety of azalanstat. They were found to be highly selective for the HO-1 isozyme (stress induced) and had substantially less inhibitory potency toward HO-2, the constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 25 publications
3
58
0
Order By: Relevance
“…In previous reports, we described the selective inhibitory effects of imidazole-dioxolane compounds on HO (QC-1 and QC-13) and HO-1 (QC-13) in vitro Vlahakis et al, 2006). The calculated logP values for these inhibitors (QC-1 ϭ 3.97; QC-13 ϭ 3.27) suggested that they should cross membrane barriers and be effective in intact cell preparations as well as in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…In previous reports, we described the selective inhibitory effects of imidazole-dioxolane compounds on HO (QC-1 and QC-13) and HO-1 (QC-13) in vitro Vlahakis et al, 2006). The calculated logP values for these inhibitors (QC-1 ϭ 3.97; QC-13 ϭ 3.27) suggested that they should cross membrane barriers and be effective in intact cell preparations as well as in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…32 We have performed in vivo studies using azalanstat, a dioxolane compound, and found that it can inhibit in vivo HO activity, but only at a high dose (500 mmol kg À1 body weight), and also can induce HO-1. 34 Because these compounds were first designed as inhibitors of cholesterol production by lanosterol 14-a-demethylase, the effects of inhibiting this important pathway may preclude their use in a developing newborn, and as such have been proposed as only pharmacological tools for studying HO-1 and CO. 32,33 Although major differences exist between HO-1 and HO-2, each isoenzyme is evolutionarily conserved in the primary amino-acid and nucleotide sequences, with homology between HO-1 and HO-2 being B42%. As mentioned above, the Hmox1 gene responds to all types of stimuli, many of which have in common the association with oxidative stress; in contrast, HO-2 is responsive mainly to adrenal glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Heme oxygenase inhibitors developed more recently include the imidazole-dioxolanes which have been shown to selectively inhibit the mammalian HO-1 (inducible) versus the HO-2 (constitutive) isoform. 47 The dioxolane inhibitors were developed by synthetic modification of the lead compound azalanstat, an inhibitor of lanosterol 14R-demethylase, a fungal CYP and a critical enzyme in the lanosterol biosynthetic pathway. 48 While these inhibitors are selective in that inhibition of sGC, NOS, and the CYP isoforms 3A1/3A2 and CYP2E1 were not observed in vitro, it is hypothesized that by focusing on developing small-molecule inhibitors that bind specifically to the apoprotein rather than compounds that coordinate to the heme iron, we can further increase the selectivity toward HO.…”
Section: Discussionmentioning
confidence: 99%